Care for hospitalized elderly patients: Implications for nursing team - Meneguin, Silmara [UNESP]; Banja, Paula Fernanda Tieko [UNESP]; Ferreira, Maria de Lourdes da Silva [UNESP] (Universidade de Estado do Rio de Janeiro, 2017)
Objectives: to apprehend the perception of nursing professionals about the meaning of being elderly and to identify the facilities and difficulties faced in caring for hospitalized elderly patients. Method: qualitative research, with 34 nursing professionals, working in a medical clinic ward, at a public hospital in São Paulo State, Brazil. Data were collected through a semi-structured interview, and submitted to the content analysis Results: the perception of the elderly was related to age, physical appearance, degree of depend-ence, lack of affection and insecurity. Facilities were related to disease acceptance, treatment, passivity and trustiness in the team. Dependence, habits, relationship with the companions, coexistence with the abandonment and insufficient time for the care were considered limiting factors for the care. Conclusion: the study participants have stereotyped perception of the elderly; difficulties and facilities in care are associated to the aging process, illness and institutionalization.
El cuidado de los ancianos hospitalizados: Implicaciones para el personal de enfermería
Cuidado ao paciente idoso hospitalizado: Implicações para a equipe de enfermagem
Keywords: Aged; Aging; Hospitalization; Nursing care